Preparation and characterization of Phthalocyanine Blue encapsulated with silane coupling agent for blue light curable inkjet printing of textiles. (April 2017) - Wang, Chenglong; Wang, Lili; Huang, Yi; Nan, Xuying; Fan, Qinguo; Shao, Jianzhong
Abstract: A novel reactive organic pigment complex was prepared by 3-(Trimethoxysilyl) propyl methacrylate encapsulated on the surface of the organic pigment. The preparation conditions of the reactive organic pigment complex were optimized and the properties were characterized by FT-IR, DLS and UV–vis. The reactive organic pigment complex was used in blue-light curable pigment inks. The results showed that the photo-polymerization performance of the novel blue light curable pigment ink system was markedly increased in comparison with conventional pigment-based ink systems. The physical shielding effect of pigment particles on photo-polymerization performance can be reduced by increasing the photoinitiator concentration and irradiation intensities. The colorfastness to crocking of printed fabric was remarkably improved. However, the particle size of reactive organic pigment complex was slightly increased. Graphical abstract: Highlights: A novel reactive organic pigment complex was prepared by MPS encapsulated on the surface of the pigment. The physical shielding effect can be reduced by increasing the photoinitiator concentration and irradiation intensities. The colorfastness to crocking of the printed fabric with reactive organic pigment complex was improved.